Palladium incorporation at the anode of thin-film solid oxide fuel cells and its effect on direct utilization of butane fuel at 600 °C. (1st June 2019) - Thieu, Cam-Anh; Ji, Ho-Il; Kim, Hyoungchul; Yoon, Kyung Joong; Lee, Jong-Ho; Son, Ji-Won
Graphical abstract: Highlights: The fuel flexibility of thin-film-based solid oxide fuel cell is studied. Sputtering and infiltration are combined to add Pd at different anode positions. Thin-film-based cells were operated over butane direct utilization of at 600 °C. Pd appears to contribute to water-gas shift and steam reforming reaction. Pd improves electrochemical reaction through increasing hydrogen supply. Abstract: Fuel flexibility, which is one of the most important advantages of the solid oxide fuel cell, can be compromised at lower operating temperatures. Thus in this study, normal butane is selected as the fuel and multiscale-architectured thin-film-based solid oxide fuel cells are operated in direct butane utilization mode at T = 600 °C. Palladium (Pd) is chosen as the secondary catalyst to assist the reforming of the butane and is inserted at different positions at the anode. By combining two different Pd insertion methods, sputtering and infiltration, four different thin-film-based solid oxide fuel cells were prepared: (1) the cell without Pd (Ref-cell); (2) the cell with Pd at the anode functional layer, which was fabricated by alternating sputtered Pd layers with pulsed-laser deposited NiO/yttria-stabilized zirconia layers (Pd-S-cell); (3) the cell with Pd at the anode support, which was fabricated by infiltration (Ref-I-cell); and (4) the cell with Pd at both the anode functional layer and anode support (Pd-S-I-cell). As expected, different Pd distributions were observed along the thickness of the anode. The Pd-S-I-cell showed significant enhancement in performance and durability. Approximately three times cell performance enhancement for the best case is observed in comparison with that of the Ref-cell. The Pd distribution, not only at the anode functional layer but also at the anode support, appears to have accelerated the electrochemical and thermochemical reactions. In addition, a lesser degree of carbon deposition was observed at the anode of the Pd-S-I-cell as compared with the case of the others.